AB1385-HPR TRUNK STRENGTH AND SPINAL MOBILITY IN SPONDYLOARTHRITIS PATIENTS. (June 2019) - Mits, Sophie De; Deroo, Liselotte; Craemer, Ann-Sophie De; Renson, Thomas; Willems, Tine; Danneels, Lieven; Carron, Philippe; Bosch, Filip van den; Elewaut, Dirk
Abstract : Background: Spondyloartritis (SpA) can seriously affect spinal mobility and trunk strength. Even though exercise therapy is considered one of the keystones of non-pharmacological treatment 1, guidelines on exercise programs remain vague due to a lack of objective measurements of physical parameters such as trunk mobility and strength. Data on these parameters are scarce for both axial and peripheral SpA-patients (axSpA and perSpA pts). Objectives: The aim of this study was to measure trunk strength and spinal mobility in SpA-pts and compare these parameters to healthy subjects matched for gender and age and to determine differences between the pts when grouped based on symptom duration and on presence of radiographic sacroiliitis. Methods: SpA-pts of the Be-Giant cohort were consecutively asked to participate in the study. After informed consent, BASDAI, BASFI and BASMI were evaluated. To measure trunk and cervical strength, pts performed 2 repetitions of a maximal isometric contraction for flexion, extension, lateral flexion and rotation on the David Back devices (DBD) after measuring the spinal mobility in these directions. The maximum value of the 2 repetitions was kept for further analysis. For assessments of lateral flexion and rotation, measured with the DBD, the mean was calculated for right and left measurements. Spinal mobility and trunk strength were compared with a healthy reference population, matched for gender and age by means of Wilcoxon singed-rank tests. When comparing the perSpA with the r-axSpA and the nr-axSpA, a Kruskal Wallis test was used. A Mann-Whitney U test was used to check for differences between groups based on symptom duration. Results: Thirty-one SpA-pts participated of which 18 were male (58%). Twenty-four (77%) were classified as axSpA and 7 (23%) as perSpA. Six (19%) of the axial pts had radiographic sacroiliitis and 18 (58%) were non-radiographic. Median time since diagnosis was 5 years and median symptom duration was 7.8 year. Mean age of the pts was 41 years (range: 21 58 years) and their BMI was on average 24 (range: 17-33). Averages for BASDAI, BASFI and BASMI were 2.6 (range 0.0-6.0), 1.7 (range 0-6.8) and 0.9 (range 0.6-4.4) respectively. SpA-pts showed decreased mobility for cervical flexion (p<0.001), extension (p<0.001) and rotation (p<0.001) and trunk rotation (p=0.001) compared to the healthy population. Cervical and trunk muscle strength was significantly decreased in SpA-pts in all directions compared to the reference population (flexion: p=0.02, other directions: p<0.001). When comparing mobility and strength based on groups by radiographic axial or peripheral involvement, no significant differences could be detected. When grouped based on symptom duration, the pts with longer standing symptoms (>7.8 year) show a significant reduced mobility for cervical extension (p=0.004) and rotation (0.049) and lumbar rotation (p=0.033) and a trend toward significance for lumbar extension (p=0.066) compared to those with shorter symptom duration (<7.8 year). For strength no significant differences could be demonstrated between the groups. Conclusion: Results of this study showed that SpA-pts have less mobility and decreased strength when compared with healthy gender- and age-matched controls. When comparing within the patient group, based on radiographic involvement, there were no differences neither for mobility or strength. Only discrete differences were found for mobility and no differences for strength when grouped based on symptom duration. Therefore, rehabilitation of all SpA-pts should focus not only on mobility but should include trunk strengthening exercises as well. References: [1] van der Heijde D. et al. 2016 Ann Rheum Dis 2017;76;978-991 Disclosure of Interests: Sophie De Mits: None declared, Liselotte Deroo: None declared, Ann-Sophie De Craemer: None declared, Thomas Renson: None declared, Tine Willems: None declared, Lieven Danneels: None declared, Philippe Carron: None declared, Filip van den Bosch Consultant for: AbbVie, BMS, Galapagos, Janssen, Lilly, Merck, Novartis, Pfizer and UCB, Speakers bureau: AbbVie, BMS, Janssen, Lilly, Merck, Novartis, Pfizer and UCB., Dirk Elewaut: None declared